2017
DOI: 10.5713/ajas.16.0436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between behavioural responses and performance traits in laying hens

Abstract: ObjectiveThe aim of the study was to evaluate genetic correlations between the behavioural profile and performance in laying hens as an indirect answer to the question whether the observed behavioural responses are associated with increased levels of stress in these birds.MethodsThe assessment of birds’ temperament was carried out using the novel objects test. The behavioural test was conducted in two successive generations comprising 9,483 Rhode Island White (RIW) birds (approx. 4,700 individuals per generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The present study also confirms that fearfulness is one of the temperament traits differentiating the breeds from the first days of life (Table 6). This trait in animals is characterised by a high inheritance rate, which has also been confirmed in laying hens [6,7]. The study has shown that fearfulness changes over time, exhibiting a downward trend in older chicks, which may be associated with habituation to a given stimulus.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The present study also confirms that fearfulness is one of the temperament traits differentiating the breeds from the first days of life (Table 6). This trait in animals is characterised by a high inheritance rate, which has also been confirmed in laying hens [6,7]. The study has shown that fearfulness changes over time, exhibiting a downward trend in older chicks, which may be associated with habituation to a given stimulus.…”
Section: Discussionsupporting
confidence: 55%
“…As demonstrated in many studies, the level of additive variability is so high that selection for modification of chicken's temperament may bring positive effects [6,7,12]. Currently, behavioural selection is mainly targeted at reduction of aggression and pterophagy [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be debated whether the behaviour of Lg hens is associated with the large-scale production of the breed as a result of the reaction correlated between performance and behavioural traits (Rozempolska-Rucińska et al, 2017) or whether the differences are associated with the white colour of feathers. White laying hens have been shown to be reactive and demonstrate an intense hormonal and behavioural response to stress compared with brown hens (Fraisse & Cockrem, 2006;Ulitdehaag et al, 2011;de Haas et al, 2013;Pusch et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our previous studies (Rozempolska-Rucinska et al, 2017) all hens were classified according to their behaviour, to the one of 6 groups: escape (34 individuals)-birds with sudden movements, attempting to go outside the cage; avoidance (35 individuals)-birds moving away from the object but without sudden movements; avoidance-approach (35 individuals)-birds with alternate reactions: approach and moving away from the object; observation (44 individuals)-birds standing in one position with minor head or torso movements, observing the object and not approaching nor distinctly moving away from the object; approach (23 individuals)-approaching to the object, heading towards the object and observing it; pecking (29 individuals)-approaching to the object with one or multiple pecking on the object. Detailed information on the test performance and classification of laying hens to a specified group was given by Rozempolska et al, 2017aRozempolska et al, , 2017b The next step was the analysis of behavioural reactions with the use of Java-based free software, Tracker 4.95 ® (Brown, 2012) for motion analysis allowing determination of multiple movement parameters. Each video clip was analysed with a frame-by-frame method with step size of 20 frames which refers to an interval of 0.8 second.…”
Section: Methodsmentioning
confidence: 99%